High performance ultrafast thulium-doped fiber lasers - Limpert, Jens; Gebhardt, Martin; Gaida, Christian; Heuermann, Tobias; Wang, Ziyao; Jauregui, Cesar (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Ultrafast lasers that deliver intense femtosecond pulses at carrier wavelengths beyond the well-established emission bands of Yb- or Ti:Sa-based sources have become extremely popular drivers for scientific applications. It is widely known that the long wavelength is a key property to enable new strong-field experiments or to significantly improve existing ones, e.g. in the case of extreme nonlinear frequency conversion to otherwise hardly accessible spectral regions. Those spectral regions of interest range from the deep mid-infrared (based on parametric amplification in non-oxide crystals) up to the soft X-ray regime (via high-harmonic generation). In order to turn such laboratory experiments into real-world applications with improved signal-to-noise-ratios and fast data acquisition and to unlock applications within the industry sector as well, the long wavelength driving laser sources need to deliver high repetition rates and high average powers.
CRIS-Team Scopus Importer:2023-04-20